2017
DOI: 10.1021/acscatal.7b00709
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Engineering of Discrete Pt(II)···Pt(II) Interactions for Visible-Light Photocatalysis

Abstract: Visible-light photosensitizers have emerged as a sustainable and environmentally friendly medium for organic transformation. Herein, we have developed a supramolecular strategy for manipulating visible-light photosensitization and photocatalytic efficiencies. With the elaborate manipulation of aggregated Pt­(II)···Pt­(II) interactions, the discrete tetranuclear Pt complexes not only show high binding affinity (K a ∼ 106 M–1) but also feature bathochromic-shifted metal–metal-to-ligand charge transfer transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 40 publications
1
35
0
5
Order By: Relevance
“…These radicals are highly ROS, able to oxidize directly organic contaminant. In our study, the generation of O 2 • − and •OH was confirmed by the ESR spectra by using DMPO as the spin trap reagent [14], instead, TEMP was used to detect singlet oxygen and it proved electrons and holes generation during visible light irradiation [46]. highlighted a similar conclusion in their study on ternary nano-composite based on cadium sulphide (CdS), TiO2, and graphene oxide.…”
Section: Active Species and Possible Mechanismsupporting
confidence: 74%
See 2 more Smart Citations
“…These radicals are highly ROS, able to oxidize directly organic contaminant. In our study, the generation of O 2 • − and •OH was confirmed by the ESR spectra by using DMPO as the spin trap reagent [14], instead, TEMP was used to detect singlet oxygen and it proved electrons and holes generation during visible light irradiation [46]. highlighted a similar conclusion in their study on ternary nano-composite based on cadium sulphide (CdS), TiO2, and graphene oxide.…”
Section: Active Species and Possible Mechanismsupporting
confidence: 74%
“…The time of irradiation increased and the intensity of peaks decreased, after half-hour of irradiation the resulting spectrum is shown in Figure 9A. The decrease in spectrum intensity of peaks suggests that 1 O 2 radical generation occurred in the very first intervals of the photo-catalytic process that is mainly due to their nano-second lifetime [46,91,92]. 5,5-dimethylpyrroline N-oxide (DMPO) was utilized as superoxide and hydroxide radical anions (O 2 • − , •OH) spin trap.…”
Section: Active Species and Possible Mechanismmentioning
confidence: 95%
See 1 more Smart Citation
“…Transition metal complexes with triplet molecular dioxygen ( 3 O 2 ) -sensitive luminescence at room temperature have been extensively studied in the last decades, due to their broad spectrum of applications, ranging from bioimaging agents [1][2][3][4][5] and photocatalysts 6,7 to active materials in photodynamic therapy, 8,9 OLEDs, [10][11][12] and optical sensors. [13][14][15][16][17] The emission of monomeric Pt(II) complexes arises mainly from metal-perturbed ligand-centered triplet states ( 3 MP-LC) as an admixture of 3 LC and 3 MLCT character (ligand-centered * and metal-to-ligand charge-transfer d*, respectively).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 The diradical character of such excited states with enhanced metal–metal bonding interactions renders these complexes capable of performing photocatalytic C–X bond cleaving reactions. 3 , 4 The classic example, [Pt 2 (μ-P 2 O 5 H 2 ) 4 ] 4– , is a highly active catalyst for the photoinduced dehydrogenation of alcohols to aldehydes/ketones in the absence of a sacrificial electron acceptor via its long-lived 3 [5dσ*6pσ] excited state. 1 a Due to the uniqueness of the μ-pyrophosphito ligand, extending the photochemistry of [Pt 2 (μ-P 2 O 5 H 2 ) 4 ] 4– to other platinum( ii ) complexes is a non-trivial task.…”
Section: Introductionmentioning
confidence: 99%